Parliamentary agency and regional integration in europe and beyond: The logic of regional parliaments - Luciano, Bruno Theodoro [UNESP] (Taylor & Francis, 2021)
This comparative book analyses the development of regional integration parliaments in three different continents of the world. It assesses and compares the expansion and current stage of institutional development of three regional assemblies - the European Parliament, the Pan-African Parliament and the Mercosur Parliament for Latin America. Looking in particular at parliamentary agency, it aims to answer why and to what extent, these regional parliaments have developed differently in terms of their functions and legislative competences? Drawing on new and original empirical data, official documents, and secondary literature, the book focuses on the critical junctures in the trajectory of the three assemblies and argues that parliamentary agency has impacted the institutional development of the parliaments leading to diverse paths of regional parliamentarisation. This book will be of key interest to scholars and students of global and regional governance, comparative regionalism, European Union studies, legislative studies and more broadly to international relations, history, law, political economy, and international organisations.